1983
DOI: 10.1083/jcb.96.3.875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of colchicine on internalization of prolactin in female rat liver: an in vivo radioautographic study.

Abstract: Binding and internalization of 12Sl-ovine prolactin into hepatocytes of female rats was visualized by the in vivo radioautographic method (Bergeron, J. J. M., G. Levine, R. Sikstrom, D. O'Shaughnessey, B. Kopriwa, N. J. Nadler, and B. I. Posner, 1977, Prec. NatL Acad. Sci. USA, 745:051-5055). Receptor-mediated internalization of label was observed into lipoprotein-filled vesicles in the Golgi/bile canalicular region of the hepatocyte. Colchicine treatment had no effect on the internalization of label into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…1 c). Non-receptor-mediated clearance of polypeptide hormones by the proximal convoluted tubule has been previously demonstrated ( 17,40). Quantitation of the LM radioautographic observations confirmed that the binding to the glomeruli but not to the proximal convoluted tubules was specific (Table I).…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…1 c). Non-receptor-mediated clearance of polypeptide hormones by the proximal convoluted tubule has been previously demonstrated ( 17,40). Quantitation of the LM radioautographic observations confirmed that the binding to the glomeruli but not to the proximal convoluted tubules was specific (Table I).…”
Section: Methodssupporting
confidence: 56%
“…This technique of in vivo injection and radioautography has been used to visualize insulin (16), prolactin (17), calcitonin (18), parathyroid hormone (19), epidermal growth factor (20,21), atrial natriuretic factor (22), angiotensin II (23), and ACTH (24) binding to receptors on target cells in vivo. These experiments revealed previously unrecognized binding sites relevant to the physiological functions of the cognate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism seems to be behind the juxtanuclear localization of lysosomes in many cell types [Herman and Albertini, 1984;Matteoni and Kreis, 19871. Evidence has also been obtained for a role of microtubules in the transport of endosomes from the cell margin and subsequent transfer of material to lysosomes [Bergeron et a]., 1983;Oka and Weigel, 1983;Hornick et al, 19841 and finally to Golgi [Posner et al, 19821. Based on the prekent findings, cytoplasmic dynein is a clear candidate for a role in these more general motilc processes in the cells of liver and testis and probably other cell types as well [Schroer et al, 19891.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mechanisms by which peptide hormones undergo endocytosis are less thoroughly understood. Coated pits have been observed to mediate the endocytosis of certain peptide hormones but not others (Amsterdam et al, 1981; Barazzone et al, 1980; Bergeron et al, 1983; Carpentier et al, 1985; Draznin et al, 1985; Dunn and Hubbard, 1984; Jennes et al, 1983; Nilsson et al, 1983; Smith and Jarett, 1983).…”
mentioning
confidence: 95%